Design and Synthesis of a γ1β8‐Cyclodextrin Oligomer: A New Platform with Potential Application as a Dendrimeric Multicarrier. Issue 36 (22nd July 2013) - Barge, Alessandro; Caporaso, Marina; Cravotto, Giancarlo; Martina, Katia; Tosco, Paolo; Aime, Silvio; Carrera, Carla; Gianolio, Eliana; Pariani, Giorgio; Corpillo, Davide
Abstract We report the synthesis and characterization of a water‐soluble, star‐shaped macromolecular platform consisting of eight β‐cyclodextrin (β‐CD) units anchored to the narrower rim of a γ‐CD core through bis(triazolyl)alkyl spacers. The efficient synthetic protocol is based on the microwave (MW)‐promoted Cu‐catalyzed 1, 3‐dipolar cycloaddition of CD monoazides to CD monoacetylenes. The ligand‐hosting capability of the construct has been assessed by relaxometric titration and nuclear magnetic relaxation dispersion (NMRD) profiling, which showed it to be good, and this was supported by molecular dynamics simulations. To demonstrate the feasibility of obtaining supramolecular structures with high hosting ability, we designed a dimeric platform, formed by joining two nonamers through the γ‐CD cores through a bis(lithocholic acid) linker. With a view to the potential biological applications, cytotoxicity and extent of binding to human serum albumin were assessed. The properties of this dendrimeric multicarrier make it suitable for pharmaceutical and diagnostic purposes, ranging from targeted drug delivery to molecular imaging.